Evaluation of rare earth oxides doping SnO2.(Co1/4,Mn3/4)O-based varistor system - Dibb,Alessandro (2006)
The present paper aims to verify the inuence of rare earth oxide such as lanthanum (La2O3) and neodymium (Nd2O3) doping SnO2 + 0.25%CoO + 0.75%MnO2 + 0.05%Ta2O5 system. The analysis focus on microstructural inuence on electrical properties. Microstructural analysis were made by using Transmission Electron Microscopy (TEM) at different regions of the samples. From such analysis it was found that La2O3 and Nd2O3 oxides cause heterogeneous segregation and precipitation at grain boundary concerning cobalt and manganese, decreasing the nonohmic electrical properties, as discussed, likely due to the increasing of grain boundary non-active potential barriers.